Hybrid Energy Systems Model with the Inclusion of Energy Efficiency Measures: A Rural Application Perspective - Babatunde, Damilola Elizabeth; Babatunde, Olubayo Moses; Akinbulire, Tolulope Olusegun; Oluseyi, Peter Olabisi (International Journal of Energy Economics and Policy, 2018)
The wide energy supply/demand gap has led the developing economies to the operation of the captive generators. This has contributed in no small way to the carbon footprint in the developing nations. Thus, the energy management initiative could assist in reducing the menace of greenhouse gas emission. Hence, the energy policy makers and planners have unanimously proposed adoption of demand side management (DSM) technique. Thus the adoption of energy efficiency technique (EET)-a DSM measures and hybrid energy system would be essential for rural electrification. This work investigates the effect of applying energy efficiency measures in rural electrification. A case study of an un-electrified rural settlement in Ibadan, Nigeria was considered. The utilization of EET techniques reduces the emission of CO2 by 62%, while technical analysis shows the feasibility of a 100% renewable fraction electricity production. Principally, application of energy efficient techniques proved to be economically and environmentally friendly. Keywords: Energy efficiency measures; emission reduction; hybrid energy system; net present cost; renewable energy JEL Classifications: Q4, P28